Two-dimensional simulation of grain structure growth within selective laser melted AA-2024. (5th January 2017) - Lopez-Botello, Omar; Martinez-Hernandez, Uriel; Ramírez, José; Pinna, Christophe; Mumtaz, Kamran
Abstract: A two-dimensional Cellular Automata (CA) – Finite Element (FE) (CA-FE) coupled model has been developed to predict the microstructures formed during the laser melting of a powdered AA-2024 feedstock using the Additive Manufacturing (AM) process Selective Laser Melting (SLM). The presented CA model is coupled with a thermal FE model, which computes the heat flow characteristics of the SLM process. The developed model considers the powder-to-liquid-to-solid transformation, tracks the interaction between several melt pools within a melted track, and several tracks within various layers. It was found that the calculated temperature profiles as well as the simulated microstructures bared close resemblance with SLM fabricated AA-2024 samples. The developed model was capable of predicting melt pool cooling and solidification rates, the type of microstructure obtained, the size of the melt pool (with 14% error) and the heat affected zone, average grain size number (with 12% error) and the growth competition present in microstructures of components manufactured via SLM. Graphical abstract: Highlights: The developed Cellular Automata – Finite Element model accurately predicts the microstructure of components manufactured via Selective Laser Melting. The developed Finite Element model accurately predicts the melt pool size in the Selective Laser Melting Process. Cooling and solidification rates are calculated with help of the developed Finite Element model.